2022
DOI: 10.1021/acsami.2c11248
|View full text |Cite
|
Sign up to set email alerts
|

Highly Active and Stable Ni/La-Doped Ceria Material for Catalytic CO2 Reduction by Reverse Water-Gas Shift Reaction

Abstract: The design of an active, effective, and economically viable catalyst for CO 2 conversion into value-added products is crucial in the fight against global warming and energy demand. We have developed very efficient catalysts for reverse water-gas shift (rWGS) reaction. Specific conditions of the synthesis by combustion allow the obtention of macroporous materials based on nanosized Ni particles supported on a mixed oxide of high purity and crystallinity. Here, we show that Ni/La-doped CeO 2 catalysts�with the "… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 60 publications
5
6
1
Order By: Relevance
“…We suggest that these differences are due to the different initial and final states used and to the different computational methodology used for the calculations. In fact, Alvarez-Galvan et al reported a CO 2 dissociation energy barrier of 0.75 eV, which nicely agrees with our calculated value of 0.77 eV. Moreover, they also found a barrierless H 2 dissociation reaction also in line with our results.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…We suggest that these differences are due to the different initial and final states used and to the different computational methodology used for the calculations. In fact, Alvarez-Galvan et al reported a CO 2 dissociation energy barrier of 0.75 eV, which nicely agrees with our calculated value of 0.77 eV. Moreover, they also found a barrierless H 2 dissociation reaction also in line with our results.…”
Section: Resultssupporting
confidence: 93%
“…The difference is clearly due to the different Ni atom in which H 2 adsorbs as well as to the lack of the ZPE term. For instance, in this study, the molecular H 2 adsorption energy with and without the ZPE term is −0.63 and −0.75 eV, respectively, the latter being closer to the value reported by Alvarez-Galvan et al Moreover, additional deviations can arise from the inclusion or not the contribution of long-range dispersion interactions, which have been included in our calculations via the Grimme’s D3 approach, while it seems that this is not the case in the literature values. Finally, Lustemberg et al reported adsorption energies of −0.93 and −0.24 eV for H 2 O and CH 4 , respectively, which agree with our reported values.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…[10][11][12] The combination of the above mentioned characteristics established CeO 2 -supported Ni catalysts as one of the most studied and promising candidates for the CO 2 methanation reaction. [13,14] Although the factors controlling the performance of Ni/ CeO 2 methanation catalysts are far from being completely understood, there is consensus that the Ni particle size, [9,[15][16][17] the interaction at the Ni-CeO 2 interphase [16,18,19] and the reducibility of ceria [20,21] are the most critical features of the catalyst. Despite the ongoing debate on the optimal Ni particle size, [8,9,[15][16][17] there is general belief that metallic Ni is essential for CO 2 methanation, while ionic Ni deteriorates the catalytic reaction.…”
Section: Introductionmentioning
confidence: 99%